In Vitro Cytotoxic and Genotoxic Properties of Hexa Substituted New Organophosphazene Compounds - Dogan, Hacer; Bahar, Mehmet Refik; Caliskan, Eray; Koran, Kenan; Tekin, Suat; Sandal, Suleyman; Gorgulu, Ahmet Orhan (Wiley, 2019)
[Abstract Not Available]
Keywords: Organophosphazene; A2780; LNCaP; PC-3; MTT Assay; Comet Assay